“El fenómeno de tener una ley valía la batalla”. El proceso social y político de emergencia de los Sitios de Memoria en Uruguay (Clepsidra - Interdisciplinary Journal of Memory Studies, 2024)
In this paper, some research results from my master's thesis on the emergence process of Memory Sites in Uruguay are presented. Through a situational analysis of a social event that appears in the voices of the protagonists as the beginning of the struggle for these places, the social genesis of the demand for the recovery of Memory Sites is reconstructed. Using an ethnographic approach, the network of actors involved in this process is characterized, and some of the debates that arose during the analyzed process are examined.